2005
DOI: 10.1353/pbm.2005.0054
|View full text |Cite
|
Sign up to set email alerts
|

Pain and the Placebo: What We Have Learned

Abstract: Despite the recent blossoming of rigorous research into placebo mechanisms and the long-standing use of placebos in clinical trials, there remains widespread and profound misunderstanding of the placebo response among both practicing physicians and clinical researchers. This review identifies and clarifies areas of current confusion about the placebo response (including whether it exists at all), describes its phenomenology, and outlines recent advances in our knowledge of its underlying psychological and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(68 citation statements)
references
References 41 publications
2
61
2
3
Order By: Relevance
“…It is likely that most fMRI studies and particularly those that employ repeated noxious stimulation have an implicit expectancy component. Previous work has shown that expectancy for pain (versus no pain) enhances the perceived intensity of a somatosensory stimulus (Benedetti et al, 1997;Price, 1999;Sawamoto et al, 2000) and that expectancy for reduced pain (e.g., placebo) can reduce the pain reported in response to a noxious stimulus (Voudouris et al, 1990;Price et al, 1999;Colloca and Benedetti, 2005;Hoffman et al, 2005;Koyama et al, 2005). Here, we confirm and extend those studies by demonstrating that the level of expected pain intensity significantly alters perceived pain intensity when the comparison is between two noxious thermal stimuli of slightly different intensity.…”
Section: Discussionsupporting
confidence: 85%
“…It is likely that most fMRI studies and particularly those that employ repeated noxious stimulation have an implicit expectancy component. Previous work has shown that expectancy for pain (versus no pain) enhances the perceived intensity of a somatosensory stimulus (Benedetti et al, 1997;Price, 1999;Sawamoto et al, 2000) and that expectancy for reduced pain (e.g., placebo) can reduce the pain reported in response to a noxious stimulus (Voudouris et al, 1990;Price et al, 1999;Colloca and Benedetti, 2005;Hoffman et al, 2005;Koyama et al, 2005). Here, we confirm and extend those studies by demonstrating that the level of expected pain intensity significantly alters perceived pain intensity when the comparison is between two noxious thermal stimuli of slightly different intensity.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, we focused our analysis on changes in pain and pain-related disability, regardless of the treatment or mechanism of action. It is quite possible that a strong placebo effect, as is often seen in chronic pain (Seeley, 1990;Hoffman et al, 2005), contributed to the improved outcomes observed in this study. Another important question is as follows: Are the changes in left DLPFC and elsewhere related to pain modulation?…”
Section: Future Directionsmentioning
confidence: 84%
“…Previous work has shown that the prospect of reduced pain can reduce the pain reported in response to a noxious stimulus. [84][85][86][87][88] The "inclusion/ exclusion" session provided an expectation that head pain would increase during the interventions and cease immediately after cessation of the technique. However, participants had no prior expectation of the likely course of referred head pain as the technique was sustained.…”
Section: Discussionmentioning
confidence: 99%